1997
DOI: 10.1111/j.1365-2621.1997.tb12224.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Emulsifying Properties of Soy Protein Isolates Modified by Pancreatin

Abstract: Soy protein isolates (SPI) with varying degrees of hydrolysis (DH of 7, 11, 15, 17%) were produced using pancreatin. The surface hydrophobicity indices of pancreatin hydrolyzed SPI (PSPI) (34.5, 34.9, 39. 1, and 40.7 for 7, 11, 15, 17% DH, respectively) were higher than that of SPI (10.5) and control SPI (CSPI) (12.5, 11.9, 12.9, and 12.6 for 10, 60, 120, and 180 min incubation, respectively). The solubilities of PSPI at pH 4.5 were 2.7, 9.1, 11.9, and 18.7%, for 7, 11, 15, and 17% DH, respectively, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
116
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 26 publications
16
116
1
2
Order By: Relevance
“…Degree of hydrolysis values were higher than those reported for hydrolysis of legumes such as V. unguiculata (23.61%) with Alcalase 1 for 60 min (Espinosa, Chel, & Betancur, 2006), chickpea (27%) with Flavourzyme 1 for 180 min (Clemente, Vioque, Sa´nchez-Vioque, Pedroche, & Milla´n, 1999) and soy with pepsin for 60 min (11%) and 180 min (17%) (Qi, Hettiarachychy, & Kalapathy, 1997). In general, enzymes from microbial and fungal origins such as Alcalase 1 and Flavourzyme 1 have a higher catalytic activity compared to enzymes from gastric and intestinal origins like pepsin and pancreatin.…”
Section: Protein Concentrate Hydrolysismentioning
confidence: 60%
“…Degree of hydrolysis values were higher than those reported for hydrolysis of legumes such as V. unguiculata (23.61%) with Alcalase 1 for 60 min (Espinosa, Chel, & Betancur, 2006), chickpea (27%) with Flavourzyme 1 for 180 min (Clemente, Vioque, Sa´nchez-Vioque, Pedroche, & Milla´n, 1999) and soy with pepsin for 60 min (11%) and 180 min (17%) (Qi, Hettiarachychy, & Kalapathy, 1997). In general, enzymes from microbial and fungal origins such as Alcalase 1 and Flavourzyme 1 have a higher catalytic activity compared to enzymes from gastric and intestinal origins like pepsin and pancreatin.…”
Section: Protein Concentrate Hydrolysismentioning
confidence: 60%
“…In the case of whey and casein proteins on the other hand, Van der ven et al (2002) found that although foam formation showed improvement after enzymatic hydrolysis and that foam stability was poorer than it was before modification. Findings by Qi et al (1997) suggest that pancreatin modified soy protein exhibited better emulsifying activity index than the original protein, making it a potential ingredient in the emulsified foods formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein hydrolysates are promising candidate to be used as natural emulsifiers because of their safety, biodegradability, and producibility from renewable sources. Several recent studies have reported on the potent emulsifying activities of various protein hydrolysates, such as soy 5 , and potato 6 protein hydrolysates. Considering on the effects of protein hydrolysates on oxidative stability of emulsion model, however, the data are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, RBPH with different degrees of hydrolysis DH were prepared, and their abilities to retard both of phase separation and lipid oxidation in soybean O/W emulsions were observed. RBPH with rather low DH less than 10 were studied in the present work because of the previously reported disadvantages of extensively hydrolyzed peptides, including bitter taste as well as inferior emulsifying, foaming, and antioxidant activities 5,16 .…”
Section: Introductionmentioning
confidence: 99%